STUDI KAWASAN DALAM SEJARAH ISLAM DI ASIA TENGGARA - Widyatul Hidayah; Chuzaimah Batubara (Islamijah: Journal of Islamic Social Sciences, 2022)
The beginning of Muslim commercial civilization was the spread of Islam to Southeast Asia in the seventh century. The introduction of Islam led to an Islamic-style monarchy that lasted from the XIII to the XVI centuries. Because the rulers of the kingdom accepted and propagated Islam, which was then socialized and developed to the lower classes or with the pattern of the upper dawn, this country has a Muslim majority population. The growth and religious life of Brunei Darussalam and Malaysia is relatively good and safe when compared to other Southeast Asian countries such as Indonesia, Singapore, and Myanmar. The entry of Islam in Southeast Asia, not only has an effect on politics, but also socially, culturally and economically.Keywords: Islam, Southeast Asia